The Influence of Learning Methods and Media on the Teaching Effectiveness of Arabic Language Teachers - Afriza; Nurazzelena Abdullah; Kasmiati Kasmiati; Halomoan; abul maali (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2025)
This study investigated the influence of teaching methods and media on the effectiveness of Arabic language instruction by teachers in Kampar District. A quantitative correlational research design was employed, conducted in Kampar in 2022. The participants were 39 Arabic language teachers in the district. Data was collected through questionnaires, observations, and document analysis. SPSS version 26 used to analyze the data. The findings revealed a significant positive correlation between the combined use of effective teaching methods and media and the overall effectiveness of Arabic language teaching. Based on these results, it was recommended that schools provide teachers with training on strategies to enhance teaching effectiveness. Additionally, teachers should be encouraged to explore and implement innovative teaching methods and media to improve their instructional practices.